Prevalence, Determinants, and Antibiotic Resistance Patterns of Urinary Tract Infections in Antenatal Women in an Urban Resettlement Colony and Slum in Delhi, India: A Cross-sectional Study - Divya Gupta; Mongjam M. Singh; Saurav Basu; Suneela Garg; CP Baveja; YM Mala (Indian Journal of Community Medicine)
Background: Urinary tract infection (UTI) is the most common bacterial infection occurring in pregnant women with untreated, recurrent, and inadequately treated bacteriuria accentuating the risk of multiple adverse fetal and maternal health outcomes. The study objective was to determine the proportion of UTIs and their predictors along with antibiotic resistance patterns of causative organisms in pregnant women. Materials and Methods: This cross-sectional study was conducted among 348 pregnant women in an urban resettlement and slum colony. Urine samples were examined through semi-quantitative culture on plated Mac Conkey and blood agar. Antibiotic susceptibility testing was done on Muller Hinton agar using the modified Stokes’ disc diffusion method. Results: At least one symptom related to UTI was reported by 35.7% (95% CI: 30.7-41.1) of the participants. The proportion of pregnant women detected having UTI on urine culture was 7.4% (n = 24, 95% CI: 5.1-10.8) with 13 (54.2%) asymptomatic and 11 (45.8%) symptomatic cases. Overcrowding was a significant predictor of UTI. The most common organisms detected were Escherichia coli (n = 12), Klebsiella pneumoniae (n = 7), Staphylococcus aureus (n = 3), and Acinetobacter species (n = 2). Conclusions: The use of individual toilets and active screening for UTI through culture and sensitivity testing in pregnant women should be promoted in low-resource settings irrespective of symptoms. The initiation of presumptive antibiotic therapy for UTI cases in pregnant women should be restricted to painful micturition due to high false positivity of other symptoms with Nitrofurantoin being a likely preferred drug for empirical administration due to its low resistance pattern among isolated organisms.